Measuring Child Poverty in Jakarta Metropolitan Area Using a Multidimensional Perspective - Nigel Roy Tantan; Erni Tri Astuti (Proceedings of The International Conference on Data Science and Official Statistics, 2021)
This study aims to quantitatively uncover multidimensional child poverty in Jakarta Metropolitan Area, where Indonesia’s capital and its surrounding regions are located. It comprises 15 indicators in six dimensions of child wellbeing: housing, education, facility, food and nutrition, child protection, and health. It is a very alarming condition in the region that nearly one-fourth of children are deprived in at least three dimensions. These children experience, on average, 0.57 of all possible deprivations, or 3.4 deprivations, which indicates a massive high deprivation intensity. The overall deprived children are also almost two times larger than the poor children that suggest the lower monetary child poverty rate doesn’t guarantee to lower the multidimensional child poverty.